Designing a sustainable stochastic electricity generation network with hybrid production strategies - Gonela, Vinay; Salazar, Dalila; Zhang, Jun; Osmani, Atif; Awudu, Iddrisu; Altman, Barbara (International journal of production research, 2019)
This paper aims to design a sustainable stochastic electricity production network where fossil fuels-based, biomass-based, and co-firing-based production strategies are simultaneously considered in order to take advantage of all the three production strategies. A multi-objective stochastic mixed integer linear programming model is proposed to achieve economic feasibility, as well as environmental and social benefits under multiple uncertainties. The model is solved by using the improved augmented epsilon constraint method. A case study is used to illustrate the effectiveness of the proposed model. Pareto optimal analysis is conducted to understand the trade-off between economic, environmental, and social aspects of sustainability.